Qualitative spatial reasoning methodology to determine the particular domain of a set of geographic objects. (June 2016) - Torres, Miguel; Loza, Eduardo; Al-Halabi, Wadee; Guzman, Giovanni; Quintero, Rolando; Moreno-Ibarra, Marco
Abstract: Nowadays, there are many geospatial information from different sources such as satellite images, aerial photographs, maps, databases and others. They provide a comprehensive description of geographic objects. However, the task to identify the geographic domain is not an easy task, because it involves a semantic processing related to inference approaches that are based on the conceptualization of a domain. These approaches allow us to understand in a similar way that human beings recognize the geographic entities and help us to avoid vagueness and uncertainty. In this paper, a methodology to perform a qualitative spatial reasoning in geospatial representations is proposed. It is based on a priori knowledge, which is explicitly formalized by means of an application ontology. The knowledge described in the ontology is assessed according to a set of labels, belonging to any geographical domain for semantic analysis and mapping those labels to matching concepts defined in the ontology. As result, a set of geographic domains ordered by their relevance is obtained, providing a general concept directly related to the input labels, simulating the way that we perceive cognitively any geographic domain in the real world. Highlights: This work proposes an approach focused on qualitative spatial reasoning. The research determines contextual domains from a set of geographic objects. Conceptual frequency, relevance, and semantic genealogy algorithms. Conceptual frameworks to represent explicitly the knowledge of any domain. Structure and organize the semantics of the geographic context.